Enhancing Student Learning Outcomes through Formative Assessment: A Systematic Literature Review - Ramdhani, Luthfi Ilham; Triana, Dinny Devi; Madani, Faisal (Mimbar Ilmu, 2024)
The challenge of low student learning outcomes and the limitations in motivating their active involvement in learning remains a significant issue in various educational contexts. This study aims to analyze the effectiveness of formative assessment as an approach to improving student learning outcomes across different educational levels. The method used is a Systematic Literature Review (SLR) with the PRISMA framework, encompassing the analysis of 30 relevant articles from primary education to higher education. Data collection was conducted by identifying and categorizing relevant articles, then analyzing findings related to the impact of formative assessment on student learning. Data analysis was performed through synthesizing key findings from the studies analyzed. The results of the study show that formative assessment significantly contributes to improving students' understanding of the learning material, promoting critical thinking skills, increasing learning motivation, and enhancing students' active engagement in the learning process. Additionally, the study highlights the crucial role of teachers in providing relevant and constructive feedback. Challenges in implementing formative assessment include high teacher workloads, limited training, and inadequate technology support. The conclusion of this study is that formative assessment can be a highly effective tool for improving the quality of learning when supported by adequate teacher training, the development of technology infrastructure, and better integration into the curriculum.